Stressful life events preceding the onset of depression in Asian patients with major depressive disorder - Park, S.; Hatim, A.; Si, T.M.; Jeon, H.J.; Srisurapanont, M.; Bautista, D.; Liu, S.I; Chua, H.C.; Hong, J.P. (SAGE Publications, 2015)
Background: Previous studies have identified the significant role of stressful life events in the onset of depressive episodes. However, there is a paucity of cross-national studies on stressful life events that precede depression. Aims: We aimed to compare types of stressful life events associated with the onset of depressive episodes in patients with major depressive disorder (MDD) in five Asian countries. Method: A total of 507 outpatients with MDD were recruited in China (n=114), South Korea (n=101), Malaysia (n=90), Thailand (n=103) and Taiwan (n=99). All patients were assessed with the Mini-International Neuropsychiatric Interview and the List of Threatening Experiences. The prevalence of each type of stressful life events was calculated and compared between each country. Results: The type of stressful life event that preceded the onset of a depressive episode differed between patients in China and Taiwan and those in South Korea, Malaysia and Thailand. Patients in China and Taiwan were less likely to report interpersonal relationship problems and occupational/financial problems than patients in South Korea, Malaysia and Thailand. Conclusion: Understanding the nature and basis of culturally determined susceptibilities to specific stressful life events is critical for establishing a policy of depression prevention and providing effective counseling services for depressed patients.